Levantamento de harmônicas em redes de distribuição de uma concessionária de energia - Pinto, Leandro Mayron de Oliveira (2016)
To know the disorders that affect the distribution networks originating from a power utility consumers and its evolution to the power substations, comparing measurements with literature and standards exercise. Material and Methods: We conducted three stages of measurement and analysis, using a three-phase digital analyzer, was measured the harmonic profile in different feeders of a substation for seven days each, then held the same measurement in a single residence and then this residence investigated the generators appliance harmonics. Results: In the first step, measuring feeders, they had low THD's voltage and current within the limits of standard, single-family residence already had maximum voltage THD equal to 2.84 and a maximum THD current 28.7. There was predominance of 3rd and 5th harmonic voltage and the 3rd, 5th and 7th harmonic current, with a few moments of supremacy of the 2nd harmonic. Investigating the appliance, the less power with switching power supplies introduces the greatest amount of harmonics on the network. Conclusion: distribution transformers filter low voltage harmonics, serving as a barrier to the medium voltage, which were not detected significant harmonics. The measurements reveal that in any case there was a violation of the voltage THD, in either whole or individual above the limits established by regulation, yet for the current THD presented several times above acceptable limits when analyzing the low voltage. The study shows that for power substation harmonic consumers do not evolve to the middle / high voltage.